MORPHOLOGY AND PERFORMANCE OF POLYSULFONE HOLLOW-FIBER MEMBRANE - LEE, SH; KIM, JJ; KIM, SS; KIM, UY (JOHN WILEY & SONS INC, 1993)
Polysulfone hollow fiber membranes were prepared via the dry-wet spinning process from dope solutions comprised of polysulfone, n-methyl-2-pyrrolidone, polyvinyl-2-pyrrolidone, and dodecylbenzene sulfonic acid, sodium salt. Morphology and performance of the membranes were affected by the compositions of coagulant and dope solution. Pore size and the water flux of the membrane increased by the addition of dodecylbenzene sulfonic acid, sodium salt to water in the coagulation bath, due to the changes of physicochemical properties of the outer coagulant. Addition of dodecylbenzene sulfonic acid, sodium salt to the dope solution also increased the pore size. The absence of polyvinyl-2-pyrrolidone, the pore forming agent, in the dope solution resulted in a remarkable decrease of pore size of the membrane. The distance between the spinneret and coagulation bath affected the membrane structure and performance. The membranes prepared in this study were suitable for hemofiltration in terms of molecular weight cut-off characteristics.
Keywords: PHASE-SEPARATION